Analisis Pengaruh Terapi Garam Epsom terhadap Kadar Asam Urat dan Skala Nyeri pada Lansia dengan Gout Arthritis - Ressa Andriyani Utami; Ria Efkelin (STIKes MERCUBAKTIJAYA, 2022)
The elderly population is a vulnerable group because they experience the aging process and the function of the system declines. One of the health problems experienced by the elderly is gout arthritis. Gout arthritis is a disease caused by increased levels of purines that accumulate in the joints, causing joint pain. This study aims to determine the Effect of Epsom Salt Therapy on Pain Scale and Uric Acid Levels in Elderly with Gout Arthritis. The results showed that there was a significant difference between uric acid levels before and after Epsom salt therapy in patients with gout arthritis (p value 0.000) and there was a significant difference between pain intensity before and after Epsom salt therapy in patients with gout arthritis (p value). 0.000). This research is expected to be an alternative to complementary therapy in nursing care and to develop care, further research can be carried out such as massage therapy or acupuncture.